2018
DOI: 10.1038/s41598-018-27753-y
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine allows ovarian cancer cells to adapt to hypoxia and to escape from carboplatin cytotoxicity

Abstract: Ovarian cancer is the second most common gynaecologic malignancy and the main cause of death from gynaecologic cancer, due to late diagnosis and chemoresistance. Studies have reported the role of cysteine in cancer, by contributing for hydrogen sulphide (H2S) generation and as a precursor of glutathione (GSH). However, the role of cysteine in the adaptation to hypoxia and therapy response remains unclear. We used several ovarian cancer cell lines, ES2, OVCAR3, OVCAR8, A2780 and A2780cisR, to clarify cysteine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 59 publications
(53 reference statements)
5
50
0
Order By: Relevance
“…In the future, this approach may be applied to other chemoresistant cancers. Our previous studies suggested a stronger dependence of ES2 cells on GSH turnover compared with OVCAR3 cells [12,13], which was also evidenced in this study, as higher EC 50 of free l-BSO and l-BSO@PURE G4 -FA 2 were determined for ES2 compared with OVCAR3 cells. Furthermore, concerning resistance to carboplatin, we have reported that upon carboplatin exposure ES2 produce higher levels of GSH [11] together with an accelerated GSH turnover, compared with OVCAR3 [28].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the future, this approach may be applied to other chemoresistant cancers. Our previous studies suggested a stronger dependence of ES2 cells on GSH turnover compared with OVCAR3 cells [12,13], which was also evidenced in this study, as higher EC 50 of free l-BSO and l-BSO@PURE G4 -FA 2 were determined for ES2 compared with OVCAR3 cells. Furthermore, concerning resistance to carboplatin, we have reported that upon carboplatin exposure ES2 produce higher levels of GSH [11] together with an accelerated GSH turnover, compared with OVCAR3 [28].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the development of strategies to overcome chemoresistance is required for a more effective treatment of ovarian cancer [8,15,32,33]. Following our insights on ovarian cancer metabolic remodeling and therapy response [11][12][13], we posited that a FA-Rα-targeted delivery of l-BSO can be a promising strategy to revoke resistance to carboplatin (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in studies dedicated to cancer metabolism, our team showed that cysteine is beneficial for cells coping with ROS [67,68]. In monocytes, cysteine seemed to have the same role, by protecting cells against ROS effects.…”
Section: Discussionmentioning
confidence: 99%
“…While most ovarian cancer patients respond initially to treatment, acquired resistance is common, leading to tumor recurrence [2]. Cancer stem cells (CSCs) are thought to be principal drivers of ovarian cancer progression and recurrence due to their high degree of resistance to both chemotherapy and microenvironmental stressors such as hypoxia [3,4]. Thus, extensive research is focused on the molecular mechanisms that promote a CSC phenotype.…”
Section: Introductionmentioning
confidence: 99%